Extraordinary item disclosures among Malaysian listed companies: The case of pre-adoption of revised SI 8 - Abdullah, Shamsul Nahar; Ku Ismail, Ku Nor Izah; Lode, Nor Asma (2000)
This paper attempts to investigate the following issues: (i) the incidence of Els among Malaysian companies (ii)the nature of Els among Malaysian companies (iii) the relation between Eld and income smoothing, and (iv) the relation between the incidence (and relative size of Els) and firm's size, gearing and management ownership.Even though the findings of the paper may not be as useful as the reporting of Els has been restricted via the adoption of the revised SI 8, they may shed light as to the nature, extent and explanation of reporting Els among the Malaysian companies.Nonetheless, the finding will be useful to determine whether the adoption of the revised standard has any significant impact on the information content of the financial statements.Additionally, the findings may enable users to predict the characteristics of companies that are likely to get around the revised SI 8 in order to enable them to report Els.